2019
DOI: 10.1016/j.omtm.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Selective CAR-Gene Transfer Using CD4- and CD8-Targeted Lentiviral Vectors

Abstract: Chimeric antigen receptor (CAR)-modified T cells have revealed promising results in the treatment of cancer, but they still need to overcome various hurdles, including a complicated manufacturing process. Receptor-targeted lentiviral vectors (LVs) delivering genes selectively to T cell subtypes may facilitate and improve CAR T cell generation, but so far they have resulted in lower gene delivery rates than conventional LVs (vesicular stomatitis virus [VSV]-LV). To overcome this limitation, we studied the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 32 publications
4
63
0
Order By: Relevance
“…Studies have shown enhanced TE of Vectofusin-1 compared to other delivery agents such as Tat, Pen, LAH4 derivatives, KH27K, R8, FUSO, polybrene, and retronectin. 328,[351][352][353][354][355] Interestingly, a variation in the histidine sequence order or peptide length resulted in a significant change of bioactivity. A minimum length of 21 amino acids of the LAH4 peptide family was found to be necessary for successful vector delivery.…”
Section: Reviewmentioning
confidence: 99%
“…Studies have shown enhanced TE of Vectofusin-1 compared to other delivery agents such as Tat, Pen, LAH4 derivatives, KH27K, R8, FUSO, polybrene, and retronectin. 328,[351][352][353][354][355] Interestingly, a variation in the histidine sequence order or peptide length resulted in a significant change of bioactivity. A minimum length of 21 amino acids of the LAH4 peptide family was found to be necessary for successful vector delivery.…”
Section: Reviewmentioning
confidence: 99%
“…The choice of transduction enhancer and viral envelope protein can tremendously influence transduction efficiencies ( 26 ). Direct comparison of Retronectin, Vectofusin-1, and polybrene revealed that Vectofusin-1 and polybrene are beneficial for the transduction of primary NK cells using VSV-G peusdotyped LV particles and clearly outperform Retronectin.…”
Section: Discussionmentioning
confidence: 99%
“…The transduction enhancer polybrene (Sigma-Aldrich, Germany) was utilized at a concentration of 8 ÎŒg/ml and added directly to the cells prior to transduction. Vectofusin-1 (Miltenyi Biotec, Germany) was used according to the manufacturer’s instructions and, as described before ( 26 ), at a final concentration of 10 ÎŒg/ml. In brief, Vectofusin-1 and vector particles were diluted in X-Vivo10 medium without additives in a total volume of 50 ÎŒl before both solutions were mixed, incubated for 5–10 min at room temperature, and finally added to the NK cells.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, in both lentivirus studies, efficient transduction required activation of the PBMCs. Jamali et al used a transduction-enhancing cationic peptide to further increase the efficiency of the targeted lentivirus system in cultured cells 36 .…”
Section: Discussionmentioning
confidence: 99%